Standardisation of polymerase chain reaction for the detection of Salmonella typhi in typhoid fever. Issue 5 (May 1997) - Chaudhry, R; Laxmi, B V; Nisar, N; Ray, K; Kumar, D
Abstract : To improve the diagnosis of Salmonella typhi infection, a polymerase chain reaction (PCR) assay was developed for the amplification of the dH flagellin gene of S typhi. Primers were designed from dH flagellin gene sequence which will give an amplification product of 486 base pairs. In tests to study the specificity of the assay, no amplification was seen in non-salmonella strains or salmonella strains with flagellar gene other than "d". Sensitivity tests determined that 28 pg of S typhi target DNA or 3 x 10(2) target bacteria could be detected by the PCR assay. Subsequently, the PCR technique was used for detection of S typhi in blood or clot cultures from 84 patients clinically suspected of having typhoid fever, and from 20 healthy control subjects. Twenty five of 84 samples from clinically suspected cases were positive by PCR; four of which were culture negative. No amplification was seen in samples from patients who were culture positive for organisms other than S typhi or from controls. The time taken for each sample for PCR analysis was less than 48 hours compared with three to five days for blood or clot culture. PCR appeared to be a promising diagnostic test for typhoid fever.